THE INFLUENCE OF SPINING FREQUENCY ON HATCHABILITY OF VILLAGE CHICKENS EGGS - M. W. A., Kartika; Wirapartha, M.; Dewi, G. A. M. K. (Jurnal Peternakan Tropika, 2021)
This study aims to determine the effect of the frequency of spinning on the hatchability of native chicken eggs. The study used a completely randomized design (CRD) with 3 treatments and 6 replications, each with 5 native chicken eggs so that 90 eggs were used. The treatment used was the difference in the frequency of spinning  native chicken eggs during the hatching process: P1 (Spinning 1 time / day), P3 (Spinning 3 times / day) and P6 (Spinning 6 times / day). The variables observed in the study were egg index, hatchability (%), infertile eggs (%), egg shrinkage (weight loss) on day 18, percentage of fertile eggs (%). The results showed that the effect of the frequency of stanning  native chicken eggs on treatment P1, P3, and P6 was not significantly different (P> 0.05) on egg weight, egg index, fertile eggs, infertile and egg shrinkage/ weight loss, but on P3 and P6 treatments had a significant effect  (P <0.05) on egg hatchability. The conclusion of this study was that the frequency of spinning  native chicken eggs 3 and 6 times a day had a higher effect on hatchability than the spinning once a day. The frequency of egg spinning is performed 1, 3 and 6 times a day, does not affect the index of eggs, fertile eggs, infertile eggs, and weight loss of native chicken eggs in the hatching machine.     Keywords: fertility, native chicken eggs, hatching eggs, hatchability, turning frequency